Makna Keislaman dalam Film Berlatar Belakang Budaya Jawa: Perspektif Semiotika Terhadap Film Pendek Pemean - Hanani, Iman Nur; Sunaryanto; Adnan, Ahmad (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
The objective of this research is to analyze the Islamic values in a short film set in Javanese culture, namely the film Pemean. The research method is qualitative, using Charles Sanders Peirce's semiotic analysis, which consists of three concepts: signs, symbols, and interpretants. The conclusion of the study is that the short film Pemean, which was aired on the YouTube channel Paniradya Kaistimewan, is set against the cultural and environmental backdrop of Javanese Yogyakarta, yet it contains Islamic values in accordance with the Qur’an and the Prophet’s Hadith. From a semiotic perspective, the Islamic meanings based on the Qur’an and Hadith found in the short film Pemean include: the prohibition of showing off, lying, arrogance, and spreading slander; encouragement to maintain environmental cleanliness, to be content (qana’ah), to be patient, to avoid laziness, and to do good to neighbors. The implication of this research is to challenge the view that films with cultural backgrounds are inherently secular because they lack Islamic values. Films with diverse cultural settings can convey Islamic messages that can be interpreted based on the Qur’an and the Prophet’s Hadith.